2012
DOI: 10.5897/jmpr12.209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ripening on the phytochemical constituents and antioxidant properties of plantain (Musa paradisiaca)

Abstract: The present study sought to investigate the effect of ripening on the antioxidant properties and phytochemical constituents of plantain, a major staple food of global consumption. This was done by measuring the total phenolics and flavonoid content of both ripe and unripe form of plantain. Moreover, the free radical scavenging, ferric reducing and iron chelating properties of both forms of plantain were also investigated. Finally, the ability of both extracts to prevent pro-oxidant induced deoxyribose degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In recent times, there has been a surge of interest in bioactive constituents like flavonoids, owing to their antioxidant capacity which is associated with the redox properties of their hydroxyl side chain as well as the structural relationship between their different functional groups thereby empowering them to function as metal chelators, reducing agents, hydrogen donors, (Amic et al, 2003), singlet oxygen quenchers (Gomez-Alonso et al, 2003, Materska & Peruka, 2005) and free radical chain breakers (Oboh et al, 2008) Flavonoids decreased in the artificially ripened groups thus connoting a decrease in the antioxidant capacity of the fruit. The fact that unripe mango fruit has higher flavonoid content suggests that it might be recommended for diabetic and hypertensive patients as dietary intervention in the management of their pathological conditions (Ibukun et al, 2012). Present study revealed significantly lower concentrations of flavonoids, tannin, alkaloids, phytosterol and glycosides in the artificially ripened mango groups compared with the unripe but the values for each (except glycosides) were significantly higher in the calcium carbide and the polybag ripened mangoes compared to the naturally ripe mangoes .…”
Section: Resultsmentioning
confidence: 42%
“…In recent times, there has been a surge of interest in bioactive constituents like flavonoids, owing to their antioxidant capacity which is associated with the redox properties of their hydroxyl side chain as well as the structural relationship between their different functional groups thereby empowering them to function as metal chelators, reducing agents, hydrogen donors, (Amic et al, 2003), singlet oxygen quenchers (Gomez-Alonso et al, 2003, Materska & Peruka, 2005) and free radical chain breakers (Oboh et al, 2008) Flavonoids decreased in the artificially ripened groups thus connoting a decrease in the antioxidant capacity of the fruit. The fact that unripe mango fruit has higher flavonoid content suggests that it might be recommended for diabetic and hypertensive patients as dietary intervention in the management of their pathological conditions (Ibukun et al, 2012). Present study revealed significantly lower concentrations of flavonoids, tannin, alkaloids, phytosterol and glycosides in the artificially ripened mango groups compared with the unripe but the values for each (except glycosides) were significantly higher in the calcium carbide and the polybag ripened mangoes compared to the naturally ripe mangoes .…”
Section: Resultsmentioning
confidence: 42%
“…This stand appears to be validated by Sasipriya et al (2014), even suggesting that the treatments enhanced phenolics and tannins content by up to threefold and fivefold, respectively. While this is true, Ibukun et al (2012) report that ripening has a degrading effect on the polyphenolic content of plantain pulp and its antioxidant activity on hepatic and cerebral tissues of male murine models though Tsamo et al (2014) posit that upon stage 5 ripening, an increase in phenolic content precedes this reduction. The unripe pulp extracts are regarded as possessing better antidiabetic effect over overripe and ripe pulp extract (Bhinge et al 2019).…”
Section: Wound Healingmentioning
confidence: 99%
“…Plantain is consumed as an energy-yielding food, and it is ranked third after yam and cassava for sustainability in Nigeria. , It is a rich source of carbohydrates, iron, potassium, and vitamin A, but it is low in fat and proteins . Its antidiabetic properties in experimental animals have been reported. , Ginger (Zingiber officinale) is one of the most important and popular spices that is widely utilized to add flavor to foods, in addition to its nutritional and medicinal benefits. It is indigenous to South East Asia, but it is also cultivated in various countries around the world, as well as in the tropics for its edible rhizome.…”
Section: Introductionmentioning
confidence: 99%
“…9 Its antidiabetic properties in experimental animals have been reported. 10,11 Ginger (Zingiber officinale) is one of the most important and popular spices that is widely utilized to add flavor to foods, in addition to its nutritional and medicinal benefits. It is indigenous to South East Asia, but it is also cultivated in various countries around the world, 12 as well as in the tropics for its edible rhizome.…”
Section: ■ Introductionmentioning
confidence: 99%